Navigating Non-Linear Art Histories: Sophie Orlando's Case Studies of British Black Art - Ella S. Mills (Images Re-Vues)
Ella S. Mills explores new approaches in Art History, based on intersectional feminism, reviewing Sophie Orlando’s British Black Art: Debates on Western Art.